Further evidence of benefits of a (non-randomised) breast cancer screening programme: the DOM project. Issue 4 (August 1992) - Collette, H J; de Waard, F; Rombach, J J; Collette, C; Day, N E
Abstract : STUDY OBJECTIVE--The aim was to demonstrate the benefits of breast cancer screening on mortality. DESIGN--The study was an evaluation of a breast cancer screening programme by means of different approaches: (1) a case-control study, breast cancer deaths being the cases; (2) comparing the numbers of breast cancer deaths in screened and unscreened women; (3) comparing breast cancer mortality before and after start of the programme; (4) comparing breast cancer mortality in different large cities; (5) comparing screening activity with mortality reduction. SETTING--The setting was a breast cancer screening programme in the city of Utrecht, the DOM project, for women aged 50-64 years old at intake, birth cohort 1911-1925. The programme started in 1974, and there were five screening rounds up to 1984. Participation rate in the first round was 72% (14, 697 women). MAIN RESULTS--(1) Screening was protective against dying from breast cancer, odds ratio 0.52, with a stronger effect in older women and no evidence of confounding; (2) risk ratio of dying from breast cancer for women in the response group was the same as the odds ratio, 0.52; (3) breast cancer death rate after the start of the project was nearly 20% lower than before the project started; after correcting for women who could not have benefited from screening the reduction was 33%; (4) a rise in breast cancer mortality in birth cohort 1911-1925 seen in other large cities without a screening programme due to aging of the cohort was not seen in the city of Utrecht; (5) mortality reduction followed the screening activity with a time lag of approximately 5 years. CONCLUSIONS--Early diagnosis of breast cancer by mammography reduces breast cancer mortality in women 50-64 years old at intake; different approaches to the evaluation of the project give different estimates of the screening effect, making clear that the effect depends on the intensity of the programme.